Financial literacy level of Polytechnic Higher Education students in North of Portugal - Vieira, Cláudia (2022)
This paper intends to determine the level of financial literacy of students of polytechnic students of the Association of North region Polytechnics (Associação de Politécnicos do Norte - APNOR) in the different scientific areas. It also intends to verify if exist differences among the students between schools. For this purpose, a survey by questionnaire is used as data collection method, within students enrolled in the APNOR network as target population. The questionnaire consists of questions of financial inclusion and account management, expenditure planning and savings, choice and knowledge of information sources, as well as the characterization of the respondent. A sample of 1405 valid surveys were considered. The overall financial literacy rate is medium low (average 44.25%; standard deviation 9.26%). Students in the Economics, Management and Accounting area have an average ILFG higher than other enrolled in other areas. The students in Educational Sciences and Teacher Education and Architecture, Fine Arts and Design areas have the lowest ILFG. The vast majority of students showed very low levels when analyzing the ILF by the dimension related to knowledge of information (group 3). These results lead us to realize that the polytechnic institutes should promote further training to improve these transversal skills in their students.